18p deletion syndrome: Case report with clinical consideration and management - Megha Goyal; Mayuri Jain; Sachin Singhal; Kirty Nandimath (Wolters Kluwer Medknow Publications, 2017)
18p deletion syndrome is characterized by the deletion of short arm of chromosome 18. Presentation of this syndrome is quite variable with dysmorphic features, growth deficiencies, and mental retardation with poor verbal performance. Few patients even fail to thrive when malformations involving the heart and brain are severe. In the present article, we report an isolated case of 18p deletion in a 23-year-old female who for the first time reported to the hospital for dental problems. The patient was short statured with mental retardation and craniofacial, skeletal, dental, and endocrinal abnormalities. Such presentation warrants prompt diagnosis for effective management. Furthermore, genetic counseling for such patients and their families should be considered as a part of treatment itself.